Vibrational Spectroscopies for Investigating Structural and Biochemical Modifications Induced in Hard Dental Tissues by Femtosecond Laser Ablation: A Brief Review - Marianna Portaccio; Ines Delfino; Giovanni Maria Gaeta; Umberto Romeo; Maria Lepore (Compounds)
In recent years, the femtosecond laser ablation of hard dental tissues has stimulated great interest in preparing accurate and reproducible dental cavities. Many studies on the changes induced in the surface morphology, structure, and composition of human teeth have been performed using various advanced experimental techniques. Vibrational spectroscopies such as Fourier transform infrared (FT-IR) and Raman spectroscopy have been adopted for obtaining precise information about changes induced by femtosecond laser ablation in human teeth. Their two main components, dentin and enamel, have been carefully investigated. The analysis of the vibrational spectra has allowed for the identification of the optimal working parameters for efficient laser ablation processes. In the present review, a brief description of the abovementioned vibrational techniques is reported, and the principal results obtained by these two vibrational spectroscopies in the study of femtosecond laser ablated teeth are summarized and analyzed.